Enhanced disulphide bond stability contributes to the once-weekly profile of insulin icodec - Hubálek, František; Cramer, Christian N.; Helleberg, Hans; Johansson, Eva; Nishimura, Erica; Schluckebier, Gerd; Steensgaard, Dorte Bjerre; Sturis, Jeppe; Kjeldsen, Thomas B. (Nature communications, 2024)
Insulin icodec is a once-weekly insulin analogue that has a long half-life of approximately 7 days, making it suitable for once weekly dosing. The Insulin icodec molecule was developed based on the hypothesis that lowering insulin receptor affinity and introducing a strong albumin-binding moiety would result in a long insulin half-life, provided that non-receptor-mediated clearance is diminished. Here, we report an insulin clearance mechanism, resulting in the splitting of insulin molecules into its A-chain and B-chain by a thiol–disulphide exchange reaction. Even though the substitutions in insulin icodec significantly stabilise insulin against such degradation, some free B-chain is observed in plasma samples from minipigs and people with type 2 diabetes. In summary, we identify thiol–disulphide exchange reactions to be an important insulin clearance mechanism and find that stabilising insulin icodec towards this reaction significantly contributes to its long pharmacokinetic/pharmacodynamic profile. In this work, the authors described how the enhanced disulphide bond stability of insulin icodec enables its once-weekly profile. Disulphide bonds in insulin are subject to thiol-disulphide exchange in plasma leading to splitting insulin into its inactive chains, making the insulin disulfide stability crucial for its long duration of action.